Exploring Differentiated Learning in Teaching Writing at a Vocational High School: A Case Study - Hariry, Izumi Zahra; Mobit, Mobit; Saefullah , Hilmansyah (FKIP - Universitas Riau, 2025)
This qualitative case study aims to explore the implementation of differentiated learning, the challenges and solutions faced by the teacher in teaching at a vocational high school. An English language teacher participated in this study. Data were collected through observation, interview, and documentation to answer three research questions. The findings encompass four main aspects: content, process, product, and learning environment differentiation. The teacher used various strategies such as adjusting materials based on diagnostic test results, using different delivery methods and media in the writing process, allowing flexibility in final written products, and managing the classroom in an adaptive way. The challenges faced include increased workload, complexity in planning content, teaching complexity, assessment fairness challenges, and limited classroom space. To overcome these challenges, the teacher developed strategies including effective time management, planning collaboration, teaching management, clear assessment communication, and creative space management. This study shows the importance of teacher flexibility and creativity in applying differentiated learning in writing classrooms.